2020
DOI: 10.14203/mri.v45i2.575
|View full text |Cite
|
Sign up to set email alerts
|

Screening of anti-Candida albicans metabolites produced by marine sponge-associated bacteria

Abstract: This study selected bacteria with high anti-Candida albicans (CA) activity among ten bacteria isolated from marine sponges. Bacteria were cultivated using the basal medium to produce the extract. Minimum Inhibitory Concentration (MIC) microdilution broth was used as an anti-CA assay followed by TLC-direct bioautography to characterize their active compound with spray reagents. The bacteria determination was done by molecular approaches using Repetitive-Element Sequences-based-PCR (rep-PCR) and amplification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…isolates from OC HIV/AIDS patient or extract the pure lead compounds, despite the fact that previous study showed that various sponge-associated fungus from Indonesia shown anti-C. albicans activity. 30 Additionally, Aspergillus sp. LS78 linked with marine sponges effectively yielded a new aspericacids A with antifungal efficacy against non-MDR C. albicans .…”
Section: Introductionmentioning
confidence: 99%
“…isolates from OC HIV/AIDS patient or extract the pure lead compounds, despite the fact that previous study showed that various sponge-associated fungus from Indonesia shown anti-C. albicans activity. 30 Additionally, Aspergillus sp. LS78 linked with marine sponges effectively yielded a new aspericacids A with antifungal efficacy against non-MDR C. albicans .…”
Section: Introductionmentioning
confidence: 99%